Application of Flumethrin Pour-On on Reservoir Dogs and Its Efficacy against Sand Flies in Endemic Focus of Visceral Leishmaniasis, Meshkinshahr, Iran - MohammadReza Jalilnavaz; MohammadReza Abai; Hassan Vatandoost; Mehdi Mohebali; AmirAhmad Akhavan; Zabihollah Zarei; Sayena Rafizadeh; Hassan Bakhshi; Yaver Rassi (Tehran University of Medical Sciences, 2016)
Background: Visceral leishmaniasis (VL) is one of the most important parasitic zoonotic diseases in the world. Domestic dogs are the main domestic reservoirs of VL in endemic foci of Iran. Various methods, including vaccination, treatment of dogs, detection and removal of infected dogs have different results around the world. General policy on control of canine visceral leishmaniasis is protection of them from sand fly bites. The aim of this study was evaluation of pour-on application of flumethrin on dogs against blood-feeding and mortality of field-caught sand flies. Methods: Once every 20 days from May untill September 2013, the treated and control dogs were exposed with field caught sandflies for 2 hours under bed net traps. After the exposure time, both alive and dead sand flies were transferred in netted cups to the laboratory. The mortality rate of them was assessed after 24 hours. The blood-fed or unfed conditions were determined 2 hours after exposure to the dogs under stereomicroscope. Results: The blood feeding index was varied from 12.0 to 25.0 % and 53.0 to 58.0 % for treated and control dogs respectively (P< 0.0001). The blood feeding inhibition was 75.0-87.0 % and 41.0-46.0 % for the control and treated dogs (P< 0.0001), respectively.The total mortality rate was 94.0-100 % and 19.0-58.0 % respectively for the treated and control groups (P< 0.001). Conclustion: Application of pour-on flumethrin on dogs caused 90-100 % mortality until 2.5 month and inhibited the blood-feeding of sand flies.